Digital television in Italy - Padovani, Cinzia (Javnost (Ljubljana), 2007)
This paper analyses the impact of the digital transition on the television industry and market in Italy. A major concern for those interested in issues related to social cohesion and the impact of the digital transition on democratic practices is the fact that digital television platforms continue to produce a polarised market. Indeed, in Italy we are witnessing a shift from duopoly, a condition that has characterised the analogue television market, to duality, where quality TV content is migrating to pay-TV, leaving programming of lower quality on free-to-air channels. Given the fundamental function that television has played in shaping Italian democracy, the questionis how this mutation from duopoly to duality will inform the evolution of democratic practices in the country. The study includes an investigation of media legislation, an analysis of the digital television market, and an exploration of the public broadcasterćs struggle to maintain a relevant role in the digital environment. It concludes that the determination of the legislature to break down the duopoly is important, but that more government intervention will be necessary in order to ensure that quality free-to-air television becomes universally available.
Keywords: Italija; Italy; digitalne komunikacije; digital television; digitalna televizija; kvaliteta; dostopnost; enakopravnost; democracy; demokracija